Fake Meets Soul: Division Among Hawai'i's Japanese Surfers. (October 2020) - Christensen, Paul
This article examines the Japanese surf community in and around Honolulu, Hawai'i. I argue that a variety of factors, notably socioeconomic status and access to wealth, interpretation of popular media depictions that surround surfing, and a desire to project a "cool" bodily image, result in division within this community between those labeled as either "fake" or "soul" surfers. A division exacerbated by anger and frustration among Japanese soul surfers in Hawai'i at the more pervasive presence of fake surfers. This division creates wider complications with the sociopolitical complexities governing the larger surfing community's organization. The result is a contentious and sometimes confrontational mix delineated along lines of personal wealth, commitment to surfing, and adaptation to life in Hawai'i that reveals culturally influenced understandings of how self-image and sporting commitment are cultivated and maintained. Further complicating the picture is the cultural significance given surfing in Hawai'i as an influential component of native Hawaiian identity and means to resisting colonial incursion. By articulating these divisions of community around surfing as a nuanced and culturally weighty pursuit, I show the often hidden complexity governing the sport and its associated communities across Hawai'i's hallowed surf breaks and beaches.